Estado emocional en mujeres con cáncer de mama: variación experimentada después de una sesión psico-oncológica basada en el counselling y la psicología positiva - Vila Sánchez, Lídia; Font Guiteras, Antoni; Caba Vela, Lydia (Psicooncología, 2017)
Objective: Most studies on psychological intervention benefits have focused on the effects after several therapeutic sessions. The objective of this research was to describe the patients’ emotional state, and establish the possible immediate emotional effects of an individual psycho-oncological session.Method: The emotional state of 30 women with breast cancer was assessed with an ad- hoc tool that included items from the Distress Thermometer for Patients at the beginning and at the end of a psychological support session. During the session, issues that worried patients were addressed through an approach based on counselling and positive psychology.Results: The mean of emotional distress experienced during the previous week was 6.4 on the emotional thermometer, and more than half of the women had experienced multiple emotional problems during this period. After the session, the intensity of certain emotions decreased significantly in relation to the beginning of it, and the emotional distress compared to the previous week also decreased. In addition, more than half the sample experienced positive emotional states. Improvements were related to neither medical condition nor the number of previous psycho-oncological sessions.Conclusions: In light of the immediate distress relief, it is concluded that it is appropriate to refer all patients to the psych-oncology service, at least for a psychological assessment visit.
Keywords: Breast cancer; psychological intervention; psycho-oncological session; counselling; positive psychology.